Objectively Measured Weekly Physical Activity among Adolescent Boys and its Relation to Health-Related Physical Fitness - Edita Maciulevičienė; Rita Sadzevičienė; Renata Rutkauskaitė (Lithuanian Sports University, 2018)
Research background and hypothesis. The objective methods of measuring physical activity (PA) are used more and more widely in various types of research. However, in Lithuania there is a lack of such studies with adolescents. Thus, we conducted a pilot study to objectively measure boys' PA and to develop a more accurate PA assessment methodology in Lithuania. The purpose of this study was to analyse the objectively measured adolescent boys' weekly physical activity and its relation to their body composition and physical fitness. Research  methods.  The  participants  of  this  study  were  104  healthy  adolescent  boys.  Physical  activity  of schoolboys was measured using actigraphs (Tri-axis ActiTrainer Activity Monitors). The level of the intensity of physical activity was determined by calculating energy consumption in MET's. Low PA (LPA) equals up to 3 MET's, moderate PA (MPA) - 3-6 MET's, and vigorous PA (VPA) - 8 or more METs. Based on the frequency of VPA and MPA per week, the participants of this study were divided into physical activity groups. For health-related physical fitness  assessment  the  following  tests  were  used:  body  composition  (using TANITA  Body Analyser, TBF-300); flexibility (sit and reach test, Eurofitas, 2002), power (vertical jump was measured using a jump parameter gauge (SBM-1), muscular strength and endurance (modified push-up test (Suni et al., 1994)). Research results. All of the schoolboys demonstrated LPA on each day of the assessment. MPA on each day was experienced by 59.6% of the boys. No participants achieved VPA . The most frequent MPA and VPA were observed 5-7 and 1-3 days per week, respectively. Results of body composition indicated that boys experiencing VPA had lower body fat mass compared to those who experienced only MPA and LPA (p < 0.05). Analysis of physical fitness results indicated that boys who experienced VPA were better muscular in strength and endurance test (p < 0.05), but results of high jump and sit and reach test were not significantly different. Discussion and conclusion. Boys who experienced VPA at least for 3 days/week demonstrated better muscular strength and endurance results and had lower body fat content (%) (p < 0.05). For boys who did not experience MPA at least for 6 days/week, the total amount of weekly physical activity decreased and they could not produce better results in strength and endurance test (p < 0.05). Better results of boys' muscular strength and endurance were  significantly related to their body lower BMI (r = 0.279; p < 0.05) and fat mass (r = 0.387; p < 0.01). Objectively Measured Weekly Physical  Activity among Adolescent Boys and its  Relation to Health-Related Physical Fitness Keywords: physical activity, MET's, actigraphs.